Image-based atmosphere correction using dark pixel subtraction technique in Penang Island, Malaysia / Wan Noni Afida Ab Manan, Arnis Asmat and Noordin Ahmad - Ab Manan, Wan Noni Afida; Asmat, Arnis; Ahmad, Noordin (Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
Lack of study has found in emphasizing the appropriate chosen of atmospheric models with specific atmospheric condition. This study is attempting to answer whether selection of atmospheric models is based on regional atmospheric condition or geographic location. The proposed method is a combination of the radiative transfer equation and dark target subtraction technique. Two important atmospheric parameters in the radiative transfer equation which are visibility and aerosol loading are estimated from the image itself to be as an input in atmospheric modelling. ATCOR-2 was used to perform different atmospheric models (maritime and urban) which can represent regional climatic condition in Penang Island, Malaysia. By relating the determined aerosol optical thickness with visibility values, urban model at the visible (blue band) on image 2005 showed a high correlation coefficient which is r2 = 0.8896. It has been shown that determined the aerosol is highly correlated to the visibility range from 10 to 50 km. Study also found that optical satellite remotely sensed image data (Landsat TM blue band) can be used to determine the visibility value through the darkest pixel atmospheric correction algorithms.